Sport injuries of karate during training: An Epidemiologic Study in Iran - Ziaee, V.; Shobbar, M.; Lotfian, S.; Ahmadinejad, M. (Asian Journal of Sports Medicine, 2015)
injury in this sport in Iranian athletes seems different from other countries.